Op Amp applications handbook - Jung, Walter G. (Newnes, 2006)
Operational amplifiers play a vital role in modern electronics design. The latest op amps have powerful new features, making them more suitable for use in many products requiring weak signal amplification, such as medical devices, communications technology, optical networks, and sensor interfacing.